A QUESTION OF MAN’S IDENTITY: THE POTRAIT OF SOLDIER IN REBECCA WEST’S THE RETURN OF THE SOLDIER - Iin Nurul Hidayati; Supiastutik Supiastutik; Irana Astuti (Publika Budaya, 2014)
This article is made to show how gender identity is constructed in England and how the naturalized conception of gender is something unstable. Chris’s portrayal as a dependent man in the hands of women is far from the image of the soldier as the picture of manliness. It confirms that all knowledge including biological knowledge is socially constructed. Thus, the character of Chris Baldry as the symbol of masculinity is questioned in this article. Chris’ deviation occurs after coming home from the battle field because of shell shock. This malaise has made him forget the last fifteen years of his life. In war, his body is assaulted in the name of masculinity: men’s bodies are expected to put up a performance where values such as courage, fierceness, and patriotism are reflected in physical action. When suddenly performance can no longer be sustained, his gender/masculinity becomes vulnerable. Therefore, Judith Butler’s theory is used to conceive how a subject gets and loses his gender identity. This application confirms Butler’s performativity that gender is not something fixed. Key words : Gender identity, Masculinity, Performatifity